Factors Influencing Interest in Buying Electric Motorcycles in Jakarta - Permana, Baharudin Yudh; Septayudha, Arie; Nurdiansah, Ramlan; Sari, Synthia Atas (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The aim of this research is to determine the factors that influence the intention to purchase electric motorbikes in the community, find out the influencing variables, and use the results as material for decision-making for producers and also the government to develop the implementation of the use of electric motorbikes in Indonesia. This research focuses on independent variables that influence the dependent variable. Using a quantitative approach, data is collected through surveys targeting potential buyers and analyzed using statistical methods. This study highlights the importance of increasing public awareness about the benefits of electric motorbikes and optimizing government policies to encourage the use of electric motorbikes. These findings provide valuable insights for policymakers and industry players who want to accelerate the transition to sustainable transportation in Jakarta. Keywords: electric motorbike, community, transportation, buying.